Impact of Kin on Women’s Fertility in Bangladesh (Social Science Review, 2022)
The society of Bangladesh is kin oriented. The patriarchal relations along with the bondage with matrilineal kith and kin influences its overall socio-economic life of the people of Bangladesh. Specially, the rural societies of the country exhibit it is psychological and emotional attachment with the patrilineal families. However, women of rural Bangladesh combine their membership with a dual identity and make a wise use of it. Thus, families and kin relations have impact on the life and living of the individuals. In the context of Bangladesh, the reproductive behaviour of the woman has been shaped according to her social positioning, post marital residence, decision making status and wealth. This research contributed to understand the reasoning of the reproductive behaviour of the rural women and discussed on the influence of kin in determining age of fertility, gap between children and survival of the child. The research argues that the influence of close kins in women’s fertility and childcare is inevitable in Bangladesh. Thus, women’s maternal health security is much shaped through her relationships, which are often placed secretly. In depth interviews among 45 the married women of rural society have been conducted to explore their experiences with kin relations regarding reproductive decisions and persuasion.Social Science Review, Vol. 38(1), June 2021 Page 53-68